Comparative Study of Educational Policy Implementation in Indonesia and Malaysia: A Focus on Curriculum Design and Teacher Autonomy - Nasrullah (Indonesian Journal of Education and Science, 2025)
This study presents a comparative analysis of educational policy implementation in Indonesia and Malaysia, with a specific focus on curriculum design and teacher autonomy. It addresses four key research questions related to the philosophy of curriculum frameworks, institutional and cultural conditions influencing policy enactment, teacher agency in practice, and hybrid practices in border regions like Lombok–Sabah. Employing a literature review (library research) method, the study systematically synthesized peer-reviewed journal articles, government policy documents, and empirical studies published between 2013 and 2024. Thematic analysis was conducted using both deductive and inductive coding techniques, guided by qualitative content analysis methodology. Findings indicate that while both countries promote teacher autonomy at the policy level, Malaysia demonstrates stronger alignment between curricular goals and institutional support through mechanisms such as School-Based Assessment (SBA), Professional Learning Communities (PLCs), and leadership mentoring. Indonesia, by contrast, exhibits a symbolic form of autonomy under centralized policy structures, uneven teacher training access, and limited school-level capacity. In border regions like Lombok–Sabah, teachers exhibit high levels of contextual agency by integrating local culture, bilingual instruction, and grassroots collaboration into curriculum practice—demonstrating autonomy driven by necessity rather than policy. This research highlights the critical role of structural support, cultural responsiveness, and decentralization in actualizing teacher autonomy. It offers practical insights for education policymakers and curriculum developers seeking to create inclusive, adaptive, and teacher-empowering systems across diverse educational settings.